2023
DOI: 10.3390/foods13010002
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Preferences and Attitudes towards Plant-Based Milk

Wenfan Su,
Yu Yvette Zhang,
Songhan Li
et al.

Abstract: Plant-based milk (PBM) has become increasingly popular due to its environmental sustainability, health benefits, ingredient abundance, and unique taste. This study aims to identify the main factors that affect consumer preferences and attitudes towards PBM, and to examine the effect of consumer attitudes including environmental awareness, health consciousness, and food neophobia on WTP. We use the double-bounded dichotomy choice (DBDC) method to calculate consumers’ willingness to pay (WTP) for PBM. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Those without Turkish reading and comprehension skills were not included in the study. The number of participants to be included in this study was calculated as 170, with a = 0.05 margin of error and 95% test power using the G*Power program (version number 3.1), considering the studies in the literature [ 6 , 19 , 20 ]. This study was approved by the Acibadem Mehmet Ali Aydinlar University Medical Research Ethics Committee (ethical approval number: ATADEK 2024-3/124).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those without Turkish reading and comprehension skills were not included in the study. The number of participants to be included in this study was calculated as 170, with a = 0.05 margin of error and 95% test power using the G*Power program (version number 3.1), considering the studies in the literature [ 6 , 19 , 20 ]. This study was approved by the Acibadem Mehmet Ali Aydinlar University Medical Research Ethics Committee (ethical approval number: ATADEK 2024-3/124).…”
Section: Methodsmentioning
confidence: 99%
“…A two-part questionnaire was used to test the hypotheses ( Supplementary File S1 ). While preparing the survey, studies in the literature were reviewed [ 6 , 19 , 20 ]. The first part included questions examining the sociodemographic characteristics and general nutritional habits of the participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling theory, proposed by A. M. Spence in 1973, suggests that signaling refers to the transmission of precise information about the value or quality of a good through observable consumer behavior, and the production of goods is influenced by the information. When consumers are more willing to choose green products than normal products and are willing to pay higher prices for them [14,15], according to signaling theory, enterprises are impacted by this market signal [5]. Some studies have found that enterprises set up a green development strategy and strengthen their environmental protection concept.…”
Section: Environmental Protection Conceptmentioning
confidence: 99%
“…Consumers with high environmental preferences are more likely to make more environmentally friendly product choices, such as choosing green products [14]. They are also more willing to pay higher prices for green products [12,15,16]. It can be seen that existing studies are more concerned with the analysis of consumer behavior [17][18][19], and rarely link consumer behavior to the production and innovation of micro-firms.…”
Section: Introductionmentioning
confidence: 99%